2012
DOI: 10.4161/cl.23967
|View full text |Cite
|
Sign up to set email alerts
|

Search for inhibitors of endocytosis

Abstract: We discuss here the variety of approaches that have been taken to inhibit different forms of endocytosis. Typically, both non-specific and specific chemical inhibitors of endocytosis are tried in order to “classify” entry of a new plasma membrane protein into one of the various types of endocytosis. This classification can be confirmed through genetic approaches of protein depletion or overexpression of mutants of known endocytosis machinery components. Although some new compounds have been designed to be sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
291
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(299 citation statements)
references
References 57 publications
3
291
1
4
Order By: Relevance
“…To test our hypothesis, chloroquine and ammonium chloride, drugs known to impair lysosomal function, were used. Both drugs are basic compounds that neutralize the vesicular transition from endosomes to lysosomes (24,25). By inactivating lysosomal function, we found that cell surface MHC-I was still dramatically downregulated after infection, but total MHC-I levels were restored to those seen in uninfected cells (Fig.…”
Section: Resultsmentioning
confidence: 62%
“…To test our hypothesis, chloroquine and ammonium chloride, drugs known to impair lysosomal function, were used. Both drugs are basic compounds that neutralize the vesicular transition from endosomes to lysosomes (24,25). By inactivating lysosomal function, we found that cell surface MHC-I was still dramatically downregulated after infection, but total MHC-I levels were restored to those seen in uninfected cells (Fig.…”
Section: Resultsmentioning
confidence: 62%
“…The reduced cellular uptake at 4 °C clearly indicates that cellular uptake of cRGD‐CPN6 is energy dependent. As chlorpromazine can inhibit clathrin‐mediated endocytosis, nocodazole is caveolae‐mediated endocytosis inhibitor, and genistein can inhibit both clathrin‐ and caveolae‐mediated endocytosis,56, 57 these results clearly indicate that cRGD‐CPN6 enters MDA‐MB‐231 cells mainly through energy dependent clathrin‐mediated endocytosis pathway. Moreover, the pretreatment of LY294002 hardly affected cRGD‐CPN6 cellular uptake, revealing that micropinocytosis is not involved.…”
Section: Resultsmentioning
confidence: 85%
“…Cytochalasin D is an inhibitor of phagocytosis and macropinocytosis that disrupts actin filaments (36,37). When TLR2 KO macrophages were treated with cytochalasin D and infected with live M. pneumoniae, TNF-␣ induction was inhibited in comparison with that seen with control dimethyl sulfoxide (DMSO)-treated cells, whereas the induction was not decreased in WT macrophages (Fig.…”
Section: Resultsmentioning
confidence: 94%